Influence of supplemental grain type on forage utilization by beef steers consuming early summer bluestem - Vanzant, E.S.; Cochran, R.C.; Beharka, A.A.; Avery, T.B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Supplementation of early summer bluestem with low levels of corn, wheat, or sorghum grain had no effect on forage intake, forage digestibility, or total dry matter digestibility in beef steers, compared with a regimen of no supplementation. Increased total dry matter intakes for the supplemented steers reflected supplement consumption.
Keywords: Beef; Forage; Steers; Bluestem